Cost effectiveness analysis of total laparoscopic hysterectomy versus total abdominal hysterectomy for uterine fibroids in Western China: a societal perspective - Jinjuan Yang; Xiaojing Fan; Jianmin Gao; Dan Li; Yongjian Xu; Gang Chen (BMC, 2022)
Abstract Background As a common female pelvic tumor, uterine fibroids remain the leading cause for hysterectomy in China. Hysterectomy provides a good surgical treatment of uterine fibroids, and it guarantees the removal of all uterine fibroids without lower risk of recurrence. This study compares the cost effectiveness of total laparoscopic hysterectomy (TLH) versus total abdominal hysterectomy (TAH) for women with uterine fibroids from a societal perspective. Methods An economic analysis was conducted in 392 patients (TLH n = 75; TAH n = 317), including all relevant costs over a 12-month time horizon. Primary outcome was major surgical complications; secondary outcomes were postoperative discomfort symptoms and time of return to normal activities. Clinical, outcomes and costs data were collected from medical records, telephone survey and financial information system. Generalized linear models were used to assess costs and outcomes differences between the two groups. Incremental cost effectiveness ratio (ICER) was used to estimate the cost effectiveness. Results Mean direct costs were $2,925.71 for TLH, $2,436.24 for TAH, respectively. Mean indirect costs were $1,133.22 for TLH, $1,394.85 for TAH, respectively. Incremental societal costs were $256.86 (95%CI: 249.03-264.69). Mean differences in outcome were: 4.53% (95%CI: 4.35-4.71) for major surgical complications; 6.75% (95%CI: 6.45-7.05) for postoperative discomfort symptoms; 1.27 (95%CI: 1.23-1.30) weeks for time to return to normal activities. ICER of TLH was $5,669.16 (95%CI: 5,384.76-5,955.56) per complication averted, $3,801.54 (95%CI: 3,634.81-3,968.28) per postoperative discomfort symptoms averted and $202.96 (95%CI: 194.97-210.95) per week saved to return to normal activities. Conclusions TLH is cost effective compared with TAH in preventing additional complications based on our estimated conservative threshold in China. The findings provide useful information for researchers to conduct further cost effectiveness analysis based on prospective study which can provide stronger and more evidence, in China. In addition, the data may be useful for Chinese health care policy-makers and medical insurance payers to make related health care decisions.